Urgent endoscopy in patients with “true foreign bodies” in the upper gastrointestinal tract – a retrospective study of the period 1994–2018 - Skok, Pavel; Skok, Kristijan (Zeitschrift für Gastroenterologie, 2020)
Aim The aim of our study was to determine the frequency of patients with “true foreign bodies” in the upper gastrointestinal tract and to evaluate the success of urgent endoscopic procedures in removing these objects.Materials and methods The retrospective study includes patients in which urgent endoscopic investigations of the upper digestive tract were performed in a 23-year period, from 1st January 1994 to 1st January 2018.Results Altogether 13 196 patients were investigated: 5147 (39 %) females and 8049 (61 %) males, mean age 62.8 years, SD ± 18.5 years, range 1–106 years. In only 172 patients – 1.3 % of all subjects – true foreign bodies were detected (in range from 1–8) in the esophagus or stomach. In these patients, a total of 242 endoscopic procedures were performed. In 95.9 % the foreign bodies were removed endoscopically (165/172 patients); in 7 cases (4.1 %) the endoscopic procedures were not successful. Among the foreign bodies removed were various metal or plastic objects: hooks, batteries, coins, keys, screws, razor blades, lighters, buttons, toys, 3 toothbrushes as well as impacted safety pins. In patients with successful endoscopic removal, no significant complications were noted. In 12 patients (12/165, 7.2 %), hemorrhages from the region of the esophagogastric junction or stomach were observed; endoscopic hemostasis was performed in 10/12 patients.Conclusions Urgent endoscopy has proved successful in removing true foreign bodies from the upper gastrointestinal tract in the analyzed period. Different factors affect the success of urgent intervention, the most important being adequate experience, skills, and patience of the endoscopic team.
Keywords: true foreign bodies; upper gastrointestinal tract; urgent endoscopy; extraction; complications